Migrant Social Workers, Foreign Credential Recognition and Securing Employment in Canada: A Qualitative Analysis of Pre-Employment Experiences - Fulton, Amy; Pullen-Sansfaçon, Annie; Brown, Marion; Éthier, Stephanie; Graham, John (Canadian Social Work Review / Revue canadienne de service social, 2016)
Canada is a culturally diverse receiving country for transnational migration, and social workers are among the professional migrants who arrive in Canada each year. This article draws on findings from a four-year, grounded theory study on the professional adaptation processes and experiences of migrant social workers (n = 66) in the Canadian context. Study findings highlight a range of internal (personal) attributes and external (contextual) elements that interact to serve as either protective or vulnerabilizing factors during the pre-employment phase of professional adaptation. The focus of this article is to describe the interactions of protective and vulnerabilizing factors associated with the experience of obtaining recognition of foreign credentials and securing employment as a social worker in Canada. The findings demonstrate that migrant social workers in Canada face significant barriers in these two pre-employment phases of professional adaptation. A range of research and policy implications is identified. In particular, we highlight the disconnect that exists between Canada’s migration-friendly policies, and the lack of organizational and governmental supports and services to facilitate successful labour market integration of migrant social workers.